2015
DOI: 10.4103/0975-962x.155877
|View full text |Cite
|
Sign up to set email alerts
|

Role of human papillomavirus in oral squamous cell carcinoma and oral potentially malignant disorders: A review of the literature

Abstract: Human papillomaviruses (HPVs) are epitheliotropic viruses with an affinity for keratinocytes and are principally found in the anogenital tract, urethra, skin, larynx, tracheobronchial and oral mucosa. On the basis of high, but variable frequency of HPV in oral squamous cell carcinoma (OSCC), malignant potential of HPV infection has been hypothesized but not definitely confirmed. The aim of this review was to highlight the genomic structure and possible mechanism of infection and carcinogenesis by HPV in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 61 publications
6
81
0
2
Order By: Relevance
“…HPV has a special tropism for basal keratinocytes, and the viral genome undergoes episomal replication during the initial phase of infection, with a few copies of viral DNA per host cell present [7]. The episomal form acts as a reservoir of infected cells and is responsible for the latent state of infection [7], however not all contact with HPV may became productive infection; the host's immune system is sometimes capable of keeping the virus in latency, or it may be sufficient to eliminate the virus before it integrates into the host cell genome [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV has a special tropism for basal keratinocytes, and the viral genome undergoes episomal replication during the initial phase of infection, with a few copies of viral DNA per host cell present [7]. The episomal form acts as a reservoir of infected cells and is responsible for the latent state of infection [7], however not all contact with HPV may became productive infection; the host's immune system is sometimes capable of keeping the virus in latency, or it may be sufficient to eliminate the virus before it integrates into the host cell genome [25].…”
Section: Resultsmentioning
confidence: 99%
“…For a long time it was believed that HPV could not be transmitted to various locations of the body through the blood, however, various studies have demonstrated that the DNA of HPV may be found in the blood circulation, including the peripheral blood mononuclear cells (PBMC), serum, plasma, umbilical cord and arterial blood [8]. Blood plasma has been shown to be an attractive medium for the detection of infection by HPV, since it is a non-invasive method, and blood is the only fluid that is in direct contact with all the organs [9], however, there are no studies that have made the association of the rate of detection of HPV in blood plasma with that of tissue obtained from patients with oral leukoplakia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV 16 antibodies are said to contribute to the increased risk of HPV associated oral cancer [13]. However, malignant potential of HPV is hypothesised but not definitely confirmed [14]. Various studies on the HPV prevalence accounting to the development of oral squamous cell carcinoma have also been done in countries like-Chile [15], China, California etc.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the morphological similarities between oropharyngeal and genital epithelia, it may suggest that HPVs are more likely to play a role in the early stage of oral carcinogenesis [1] .…”
Section: Introductionmentioning
confidence: 99%